Development of Microsoft Power Point Interactive Media Based on Visual Basic for Application as Middle School Science Learning Media - Aldila Novriandami; Miftahul Jannah; Annisa Arrahma; Gusti Randa; Muhammad Nasir* (Jurnal Pendidikan Sains Indonesia, 2023)
Learning systems in the 21st century require a variety of interactive learning media. The purpose of this study is to develop an interactive microsoft power point media based on visual basic for application on vibration, wave, and sound material. This study method is a type of research and development (RD) using the ADDIE development model which consists of analysis, design, development, implementation, and evaluation stages. The population in this study at the field trial stage were all students of class VIII SMPN 1 Logas Tanah Darat. The sampling technique for this study used purposive sampling, namely determining the sample according to research needs. The research sample at the field trial stage consisted of 28 students. The data collection technique in this study was in the form of distributing questionnaires and administering tests. The validation data analysis technique uses the Aiken V validity index formula, while the analysis of practicality and effectiveness test data uses the average formula. The results of this study indicate that the results of the overall validity test index get an Aiken V validity of 0.86 with a high validity category. In addition, the results of the practical test analysis reached 83.25% in the very practical category. The results of the analysis of effectiveness get the proportion of 82.14% so that the developed media is effective. Thus it can be concluded that the microsoft power point interactive media based on visual basic for application developed are valid, practical and effective